Meloxicam ameliorates the systemic inflammatory response syndrome associated with experimentally induced endotoxemia in adult donkeys - Mendoza Garcia, Francisco Javier (J Vet Intern Med, 2020)
BACKGROUND: Little information is available about endotoxemia in donkeys. Characterizing the systemic inflammatory response (SIRS) to lipopolysaccharide (LPS) in donkeys would provide valuable clinical and therapeutic information. The effects of meloxicam on endotoxemia have not been studied in this species. OBJECTIVES: To study the pathophysiology and gene expression associated with experimentally induced endotoxemia, and evaluate the effects of meloxicam on experimentally induced endotoxemia in donkeys and in equine monocyte cultures. ANIMALS: Six healthy adult female donkeys. METHODS: Endotoxemia was induced by an IV infusion of LPS for 30 minutes. Animals either received 20 mL of saline or 0.6 mg/kg of meloxicam IV after LPS infusion. The experiments lasted 6 hours. Blood samples were collected serially for hematology, serum biochemistry, interleukin measurement, and leukocyte gene expression analysis. Vital signs were recorded throughout the study. Monocyte cultures were used to test the effects of meloxicam on LPS‐activated monocytes. RESULTS: Lipopolysaccharide induced fever, leukopenia, and neutropenia of similar magnitude in both groups, but meloxicam attenuated increases in plasma lactate, tumor necrosis factor‐alpha (TNFα), and interleukin 1β concentrations compared to controls. No differences were detected between groups for cytokine mRNA expression. Furthermore, meloxicam decreased TNFα release in LPS‐activated monocyte cultures. CONCLUSIONS AND CLINICAL IMPORTANCE: Meloxicam could be a feasible option for the treatment of endotoxemia and SIRS in donkeys. Additional studies are necessary to investigate possible meloxicam‐related posttranscriptional regulation and to compare this drug with other nonsteroidal anti‐inflammatory drugs (NSAIDs) in animals with endotoxemia.